LAND CONFLICT IN PALM OIL LAND PROCUREMENT IN INDONESIA: FEATURES, ISSUES AND APPROACHES - Dahlan, Nuarrual Hilal Md; Yusuff, Yusramizza Md Isa; Khalid, Al-Hanisham Mohd (International Journal of Supply Chain Management, 2019)
Malaysia currently accounts for 39% of world palm oil production and 44% of world exports. Being one of the biggest producers of palm oil, Malaysia has an important role to play in fulfilling the global demand for palm oil. With the growing global demand for palm oil, Malaysian Multinational Enterprises (MNEs) have embarked on the expansion of palm oil plantations by venturing into cross border palm oil plantation ventures including Indonesia. Nonetheless the cross border venture may not an easy project, as the MNEs have encountered unprecedented challenges. Currently, land conflict in palm oil land procurement in Indonesia is one of the main hindrances for Malaysian MNEs implementing investment in Indonesia. This issue if not resolved can lead to the failure of the MNEsâ?? investment and may affect the FDI flows into Indonesia. The main objective of this paper is to explain the issue of land conflicts in palm oil land procurement faced by the Malaysian MNEs in Indonesia. This paper will reveal the approaches that have been taken to address the problems. Qualitative social and legal research methodologies were used in this research. From this, certain information can be generated to show the severity of the problems arising from land conflict in palm oil land procurement in Indonesia and the approaches that have been taken by the stakeholders to deal with the problems. The findings of the research will significantly enhance the performance of the Malaysian MNEs in its internationalization of palm oil plantation ventures.